Progress in Ultrafast Intense Laser Science XIV (Progress in Ultrafast Intense Laser Science, 2018)
This 14th volume in the PUILS series presents up-to-date reviews of advances in Ultrafast Intense Laser Science, an interdisciplinary research field spanning atomic and molecular physics, molecular science, and optical science, which has been stimulated by the rapid developments in ultrafast laser technologies. Each chapter begins with an overview of the topics to be discussed, so that researchers unfamiliar to the subfield, as well as graduate students, can grasp the importance and appeal of the respective subject matter; this is followed by reports on cutting-edge discoveries. This volume covers a broad range of topics from this interdisciplinary field, e.g. atoms and molecules interacting in intense laser fields, laser-induced filamentation, high-order harmonics generation, and high-intensity lasers and their applications. .